2012
DOI: 10.3892/etm.2012.490
|View full text |Cite
|
Sign up to set email alerts
|

Sequence polymorphisms of the mitochondrial displacement loop and outcome of non-small cell lung cancer

Abstract: Abstract. Accumulation of single-nucleotide polymorphisms (SNPs) in the displacement loop (D-loop) of mitochondrial DNA (mtDNA) may be associated with disease outcome. Our team investigated the prediction power of D-loop SNPs in non-small cell lung cancer (NSCLC) outcome. In an overall multivariate analysis, allele 16390 was identified as an independent predictor for NSCLC outcome. The length of survival of patients with allele 16390A was significantly shorter than that of patients with allele 16390G (relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…However, none of the mtDNA variations were identified as independent predictors of overall survival. The association between mtDNA polymorphisms and prognosis has been analysed in various types of cancer (7,32,33). Wang et al (7) investigated the predictive power of D-loop single nucleotide polymorphisms (SNPs) in patients with HCC, and two SNP sites (nucleotides 150 C/T and 146 T/C) were identified by the log-rank test as statistically significant predictors of HCC survival.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the mtDNA variations were identified as independent predictors of overall survival. The association between mtDNA polymorphisms and prognosis has been analysed in various types of cancer (7,32,33). Wang et al (7) investigated the predictive power of D-loop single nucleotide polymorphisms (SNPs) in patients with HCC, and two SNP sites (nucleotides 150 C/T and 146 T/C) were identified by the log-rank test as statistically significant predictors of HCC survival.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation during carcinogenesis causes ROS overproduction and implicates mtDNA damage. In NSCLC, there are frequent alterations in mtDNA D-loop which regulates mtDNA replication and expression and the D-loop SNPs (e.g., 16390A) are prognostic markers for NSCLC outcome (Ding et al 2012). The majority of the coding mtDNA mutations in lung cancers targeted complex I, and a mutation in the ND5 (G13289A) of the complex I forced its overexpression and led to lung cancer cell proliferation (Dasgupta et al 2012).…”
Section: Lung Cancermentioning
confidence: 99%
“…We found that the highly polymorphic sequence in D‐loop that might be related to the breast cancer risk, esophageal squamous cell carcinoma, non‐Hodgkin lymphoma, kidney cancer, and lung cancer . But few studies focused on the relationships between coding region of mtDNA and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…14 We found that the highly polymorphic sequence in D-loop that might be related to the breast cancer risk, esophageal squamous cell carcinoma, non-Hodgkin lymphoma, kidney cancer, and lung cancer. [15][16][17][18][19][20] But few studies focused on the relationships between coding region of mtDNA and HCC. COX genes codes three subunits of respiratory complex IV, a key enzyme as the third and final enzyme of the electron transport chain of mitochondrial oxidative phosphorylation in aerobic metabolism.…”
Section: Introductionmentioning
confidence: 99%